Comparison of Rain-Driven Erosion and Accumulation Modelling of Zafit Basin on Earth and Tinto-B Valley on Mars - Vilmos Steinmann; Ákos Kereszturi (Universe)
While fluvial features are plentiful on Mars and offer valuable insights into past surface conditions, the climatic conditions inferred from these valleys, like precipitation and surface runoff discharges, remain the subject of debate. Model-based estimations have already been applied to several Martian valleys, but exploration of the related numerical estimations has been limited. This work applies an improved precipitation-based, steady-state erosion/accumulation model to a Martian valley and compares it to a terrestrial Mars analogue dessert catchment area. The simulations are based on a previously observed precipitation event and estimate the fluvial-related hydrological parameters, like flow depth, velocity, and erosion/accumulation processes in two different but morphologically similar watersheds. Moderate differences were observed in the erosion/accumulation results (0.13/−0.06 kg/m2/s for Zafit (Earth) and 0.01/−0.007 for Tinto B (Mars)). The difference is probably related to the lower areal ratio of surface on Mars where the shield factor is enough to trigger sediment movement, while in the Zafit basin, there is a larger area of undulating surface. The model could be applied to the whole surface of Mars. Using grain size estimation from the global THEMIS dataset, the grain size value artificially increased above that observed, and decreased hypothetic target rock density tests demonstrated that the model works according to theoretical expectations and is useful for further development. The findings of this work indicate the necessity of further testing of similar models on Mars and a better general analysis of the background geomorphological understanding of surface evolution regarding slope angles.